Eviction Case Filings and Neighborhood Characteristics in Urban and Rural Places: A Michigan Statewide Analysis. Issue 3 (3rd September 2021) - Goodspeed, Robert; Benton, Elizabeth; Slugg, Kyle
ABSTRACT: A growing body of evidence documents the negative impacts of eviction case filings on U.S. tenants, including forced moves, additional costs, and obstacles tenants face in finding future housing. Existing research relating evictions or eviction cases to neighborhood characteristics is geographically limited, often to metropolitan regions. In this article, we analyze nearly all eviction case filings in Michigan from 2014 to 2018 at the census tract level, allowing us to analyze how eviction filings differ in urban and rural places. Statewide, a negative binomial regression model confirms eviction case filings are related to previously hypothesized variables, including the presence of children and mortgage foreclosures. The use of interaction terms for urban tracts shows eviction filings in these tracts are more strongly related to the percentage of the population with an associate's degree or higher, vacancy rate, and mortgage foreclosures than in rural tracts. In rural areas, variables related to eviction case filings include job accessibility and the presence of mobile homes.